Real-Time Non-Invasive and Direct Determination of Lactate Dehydrogenase Activity in Cerebral Organoids-A New Method to Characterize the Metabolism of Brain Organoids? - Gal Sapir; Daniel J. Steinberg; Rami I. Aqeilan; Rachel Katz-Brull (MDPI AG, 2021)
Organoids are a powerful tool in the quest to understand human diseases. As the developing brain is extremely inaccessible in mammals, cerebral organoids (COs) provide a unique way to investigate neural development and related disorders. The aim of this study was to utilize hyperpolarized 13C NMR to investigate the metabolism of COs in real-time, in a non-destructive manner. The enzymatic activity of lactate dehydrogenase (LDH) was determined by quantifying the rate of [1-13C]lactate production from hyperpolarized [1-13C]pyruvate. Organoid development was assessed by immunofluorescence imaging. Organoid viability was confirmed using 31P NMR spectroscopy. A total of 15 organoids collated into 3 groups with a group total weight of 20-77 mg were used in this study. Two groups were at the age of 10 weeks and one was at the age of 33 weeks. The feasibility of this approach was demonstrated in both age groups, and the LDH activity rate was found to be 1.32 ± 0.75 nmol/s (n = 3 organoid batches). These results suggest that hyperpolarized NMR can be used to characterize the metabolism of brain organoids with a total tissue wet weight of as low as 20 mg (<3 mm3) and a diameter ranging from 3 to 6 mm.